2023
DOI: 10.1111/ijfs.16822
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure homogenisation improves food quality of plant‐based milk alternatives

Aien He,
Baojun Xu

Abstract: SummaryThere is a growing market for plant‐based milk products, but the consumer acceptance remains low when compared with cow milk. The aim of this study was to compare the physiochemical and organoleptic properties of plant‐based milk made from adzuki bean, adlay and oat, and to investigate the effects of using household and high‐pressure homogeniser on the physiochemical and sensory properties of plant‐based milk. The colour, pH, Brix value, suspension stability, total solid content, total soluble protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Homogenisation is also used to emulsify unstable liquids such as soy-protein-stabilised emulsions [ 20 ], condensed milk, ice cream, and other dairy products to improve their flavour and texture while extending their shelf life [ 21 ]. He et al showed that homogenisation was very effective on plant milk made from oats, adzuki beans, and adlay [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Homogenisation is also used to emulsify unstable liquids such as soy-protein-stabilised emulsions [ 20 ], condensed milk, ice cream, and other dairy products to improve their flavour and texture while extending their shelf life [ 21 ]. He et al showed that homogenisation was very effective on plant milk made from oats, adzuki beans, and adlay [ 22 ].…”
Section: Introductionmentioning
confidence: 99%